Faktor-Faktor yang Berhubungan dengan Anemia pada Ibu Hamil di Puskesmas Karanganyar - Oktaviana Rahayu; Rovica Probowati; Mursudarinah Mursudarinah (TRIAGE Jurnal Ilmu Keperawatan, 2026)
Anemia in pregnant women remains a common health problem and can pose serious risks to both mothers and fetuses. Iron deficiency is the primary cause, and the prevalence of anemia in the working area of Karanganyar Health Center is relatively high. This study aims to identify factors associated with the occurrence of anemia in pregnant women. This study employed a quantitative approach with a cross-sectional design. The sample consisted of 62 pregnant women selected through purposive sampling. Data were collected using questionnaires and analyzed with the Chi-Square test. The majority of respondents were aged 20–35 years (64.5%), had a high school education or equivalent (74.2%), and were employed (53.2%). Statistical analysis showed a significant association between the frequency of antenatal care (ANC) visits (p=0.000) and adherence to iron tablet consumption (p=0.005) with the occurrence of anemia. In contrast, age, education, employment, income, and parity were not significantly associated with anemia. Compliance of pregnant women in attending ANC visits and routinely consuming iron tablets plays an important role in preventing anemia. Health workers are encouraged to enhance education, monitoring, and motivation for pregnant women. The findings can also serve as a reference for health centers, communities, and educational institutions in developing anemia prevention strategies